PEMANFAATAN LIMBAH KULIT IKAN AYAM-AYAM (Abalistes stellaris) UNTUK BAHAN BAKU PRODUK KULIT - lndri Hermiyati; Sri Sumarni; Titik Anggaraini (Politeknik ATK Yogyakarta, 2015)
The aim of this study is to tan the leather of starry triggerfish (Abalistes stellaris) by formaldehyde. The leather of starry triggerfish was the waste which has been dumped by fishmonger around the coast of Tasik Agung in Rembang. Formaldehyde at concentration 8%, 10% or 12% was added during tanning process. The addition of 8% to 12% of formaldehyde may increase the value of tensile strength of tanned starry triggerfish leather from 47.04 kg/ cm2 up to 77.84 kg/ cm2. While the addition 8% to 12% of formaldehyde decreased the elongation value of tanned starry triggerfish leather from 56.45% to 34.51 %. The addition of 12% formaldehyde was has the best effect to the tensile strength, while the addition of 8% formaldehyde has the best effect to the elongation of tanned starry triggerfish skin. Thermal Gravimetric Analysis (TGA) has a significant influence of decreasing of weight (mass) of tanned starry triggerfish leather samples. Analysis of DTA/DSC showed the best shrinkage temperature at the tanned starry triggerfish leather tanned by 12% formaldehyde can be used as a raw material for leather product, because it has a physical character of high tensile strength and low elongation.